STUDY OF URIC ACID IN IRAN - K. Montazemi; M. Ghaffari (Tehran University of Medical Sciences, 1979)
To study the changes of serum uric acid level which is influenced by various factors including nutrition, race, socio-economic conditions age, sex, obesity and hyper lipidemia, a wide variety of survey appeared to be performed. For this study in six large provinces of Iran out of 12,524 apparently healthy individuals a total of 2,744 persons of both sexes (1,439 females, 1,305 males) were selected randomly for determination of serum uric acid. Both sexes were regarded into five age groups. The present study showed the following results: 1) Mean value of serum uric acid was significantly higher in males than in females. 2) There was a close correlation between serum uric acid and age especially in females and got rise in obsess person of both sexes. 3) Serum uric acid level was the same in females of A, B and O groups, but we found higher values in AB ones. Males of A groups had lover concentration of uric acid than O, B and AB individuals. Generally speaking, according to the present study the mean value of serum uric acid in six parts of Iran is lower than that in the other parts of the world.